Endovascular treatment of basilar artery occlusion by manual aspiration thrombectomy. (27th May 2010) - Jankowitz, Brian T; Aleu, Aitziber; Lin, Ridwan; Jumaa, Mouhammad; Kanaan, Hilal; Kostov, Dean; Hammer, Maxim; Uchino, Ken; Wechsler, Larry R; Horowitz, Michael; Jovin, Tudor G
Abstract : Background and purpose: Basilar artery occlusion remains one of the most devastating subtypes of stroke. Intravenous and intra-arterial therapy have altered the natural history of this disease; however, clinical results remain poor. Therefore, exploring more aggressive and innovative management is warranted. Methods: Six consecutive patients presenting with a basilar artery occlusion were treated with the same general algorithm of intra-arterial tissue plasminogen activator and mechanical thrombectomy with the Merci retrieval system. If complete recanalization was not achieved after two passes, manual syringe aspiration through a 4.3F catheter was employed. Results: All interventions utilizing aspiration thrombectomy resulted in recanalization, with five out of six cases displaying TIMI3/TICI3 flow and one patient resulting in complete recanalization of the basilar artery with persistent thrombus in one P2 segment (TIMI2/TICI2B). All patients survived, with five out of six independent in activities of daily living at 3 months (mRS 0–2). Conclusions: Our small case series indicates that aspiration thrombectomy performed manually through a 4.3F catheter can facilitate recanalization of basilar artery occlusion with acceptable clinical outcomes.